Mohandas : a true story of a man, his people, and an empire - Gandhi, Rajmohan (New Delhi ; New York : Penguin Books, 2007)
Biography of Mahatma Gandhi, 1869-1948, nationalist, political leade r and statesman from India.
Includes bibliographical references (p. 721-725) and index.
Keywords: Gandhi, -- Mahatma, -- 1869-1948.; Nationalists -- India -- Biography; Politicians -- India -- Biography; Statesmen; India -- Politics and government -- 1919-1947.